A novel balanced scorecard design based on fuzzy analytic network process and its application - Yuhong Cao; You Jianxin (Institute of Advanced Engineering and Science, 2014)
In this paper, wepropose a novel balanced scorecard design based on fuzzy analytic networkprocess and then conduct performance evaluation through a case study. Afteranalyzing the related works about balanced scorecard design and the algorithmof fuzzy analytic network process, we illustrate the improved balancedscorecard design. Firstly, the basic concepts for the balanced scorecardsare introduced. Secondly, four perspectives of the balanced scorecards design are provided.Thirdly, the method to promote the performance of balanced scorecard designthrough the fuzzy analytic network process is demonstrated. In the proposeddesign, a fuzzy number is represented by the left and right formation of eachdegree of membership in fuzzy analytic network process. Furthermore, the degreepossibility for a convex fuzzy number to be larger than a given convex fuzzynumbers can be represented by an effective scheme. Particularly, the basicstructure in the fuzzy analytic network process model is organized hierarchically,and the local weights of the strategies, balanced scorecard perspectives andperformance indicators can be obtained by matrix computing. Finally, a casestudy of college English classroom teaching quantitative evaluation is given todemonstrate the performance of the proposed balanced scorecard design.Experimental results show that the proposed balanced scorecard design is quiteeffective. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4804